Terrorism, Geopolitics, and Oil Security : Using Remote Sensing to Estimate Oil Production of the Islamic State - Do, Quy-Toan (Elsevier, 2018)
As the world’s most traded commodity, oil production is typically well monitored and analyzed. It also has established links to geopolitics, international relations, and security. Despite this attention, the illicit production, refining, and trade of oil and derivative products occur all over the world and provide significant revenues outside of the oversight and regulation of governments. A prominent manifestation of this phenomenon is how terrorist and insurgent organizations—including the Islamic State group, also known as ISIL/ISIS or Daesh—use oil as a revenue source. Understanding the spatial and temporal variation in production can help determine the scale of operations, technical capacity, and revenue streams. This information, in turn, can inform both security and reconstruction strategies. To this end, we use satellite multi-spectral imaging and ground-truth pre-war output data to effectively construct a real-time census of oil production in areas controlled by the ISIL terrorist group. More broadly, remotely measuring the activity of extractive industries in conflict-affected areas without reliable administrative data can support a broad range of public policy and decisions and military operations.